Foreword: Special Section on Data Center Cooling - Persoons, Tim (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Data centers account for a significant and growing fraction of the worldwide electricity demand, rising by an average of 11% per year from 2000 to a consumption of 27.1 GW in 2010, representing 1.3% of the total worldwide electricity demand. In locations with concentrated data center infrastructure, this can represent an even greater fraction of total energy consumption. For example, in Ireland in 2016, data centers consumed 250 MW or 7.8% of the all-island total; the Irish national grid operator expects this to increase to double-digit percentages by 2018. Meanwhile, the amount of digital data generated globally has multiplied on average by approximately 1.5 times per year, from 0.1 ZB in 2005 to 8.5 ZB in 2015, projected to hit 40 ZB by 2020.
Keywords: Data center; Energy comsumption; Smart & Sustainable Planet; Telecommunications